Sodium alginate-hydrogel coatings on extracorporeal membrane oxygenation for anticoagulation - Gao, Wenqing; Wang, Han; Liu, Yanwu; Tang, Qin; Wu, Peng; Lin, Tingting; Li, Tong; Sun, Di (Frontiers in Cardiovascular Medicine, 2022)
Thromboembolism caused by the use of extracorporeal membrane oxygenation (ECMO) remains common and contributes to significant morbidity and mortality during the COVID-19 pandemic. Various surface modification strategies have been proposed, showing that the methacrylated alginate (MA-SA) hydrogel layer is transparent, which is beneficial to observe the thromboembolism of the inner wall of the tube. In combination with dynamic and static blood of ECMO tube inner surface in vitro experiments, it was also demonstrated that the adhesion of blood clots to the surface was reduced, and the MA-SA hydrogel coating could significantly prolong the activated partial thrombin time and block endogenous coagulation. way to significantly improve anticoagulant performance. The favorable properties of natural polysaccharides of hydrogel coatings make them promising surface material candidates for medical devices that interface with blood. Methods for significantly improving anticoagulant performance.